Outcomes of Optilume Balloon Dilatation in patient with Urethral Stricture - SUMAIYA NOOR,; AZIZ ABDULLAH,; SEERAT UL UROOS,,; ADEEL AHMED,; JIHAND KHAN,; WAQAS AHMED,; ROHET KUMAR, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Urethral stricture occurs at a rate of 0.2%–0.6% in the male population and accounts for hundreds of millions of dollars of health care costs yearly. Aim: To determine the outcomes of optilume balloon dilatation in patient presenting with urethral stricture. Methodology: This Quasi Experimental study was conducted from January to June-2024 at Liaquat National Hospital, Karachi. At the time of enrollment demographic and clinical details were taken. All patients were screened for urethral stricture. Before procedure IPSS score was calculated. Uroflowmetry and was done to assess the Qmax and PVR. All patients with urethral stricture were undergoing optilume balloon dilatation. All patients were followed till 30 days assessment of outcomes. Results: Data were collected from 50 male patients. Mean age of the patients was 45.6±12.3 years. Baseline IPSS score was 22.0±6.8, Qmax10.5 ± 2.8 ml/sec and PVR 100.5±20.3ml. The mean IPSS score decreased from 22.0±6.8 at baseline to 7.6±5.7 post-procedure (p < 0.001), reflecting a substantial reduction in urinary symptoms. The mean maximum urinary flow rate (Qmax) increased from 10.5±2.8 ml/sec to 18.2±3.5 ml/sec (p <0.001), indicating improved urinary flow. Additionally, the mean post-void residual (PVR) volume decreased from 100.5 ± 20.3 ml to 30.4±10.2ml (p <0.001), suggesting more complete bladder emptying. Conclusion: It is concluded that Optilume balloon dilatation represents a promising therapeutic approach for urethral stricture, as evidenced by significant improvements in IPSS, Qmax, and PVR within 30 days post-procedure. Keywords: Optilume balloon dilatation and urethral stricture.